(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Analysis of some epidemiological characteristics of refractive errors in primary school students in Quang Nam province in 2023. Subjects and methods: A cross-sectional descriptive study on 1148 second and third-grade students at 5 primary schools Vo Thi Sau, Nguyen Thi Minh Khai, Kim Dong Bac Tra My, Kim Dong Tien Phuoc, and Minh Vien in Quảng Nam province in 2023. Results: The overall prevalence of refractive errors in the students was 10.2%, in which myopia accounted for the highest percentage with 6.1% in the right eye and 6.0% in the left eye. Astigmatism ranked the second with 3.0% in the right eye and 3.7% in the left eye. Hyperopia was rare, only 0.1-0.2%. Most of the students with myopia was mild (81.57%), followed by moderate myopia (17.11%) and severe myopia (1.32%). In contrast, moderate astigmatism was the highest (56.25%), followed by mild astigmatism (29.17%), severe and very severe astigmatism (14.58%). Kết luận: Tỷ lệ tật khúc xạ chung là 10,2%, trong đó cận thị là dạng tật phổ biến nhất, chiếm 6,1% ở mắt phải và 6,0% ở mắt trái; loạn thị đứng thứ hai với 3,0% ở mắt phải và 3,7% ở mắt trái; cận thị mức độ nhẹ 81,57%; tỷ lệ loạn thị mức độ trung bình 56,25%. Conclusion: The overall prevalence of refractive errors in the students was 10.2%, in which myopia accounted for the highest percentage with 6.1% in the right eye and 6.0% in the left eye; astigmatism ranked the second with 3.0% in the right eye and 3.7% in the left eye; hyperopia was rare, only 0.1-0.2%. Most of the students with myopia was mild (81.57%). In contrast, moderate astigmatism was the highest (56.25%).